Flashbulb Memories in the Communication of the Diagnosis of Visual Impairment: The Effect of Context and Content - Mª Emma Mayo Pais; José Eulogio Real Deus; Patricia Mª Iglesias-Souto; Eva Mª Taboada-Ares (MDPI AG, 2023)
The diagnosis of a child's visual impairment is remembered vividly and intensely by their parents. However, the way in which the diagnosis is communicated may affect the development and persistence of this memory. The aim of this study is to analyze the circumstances in which the first news of the diagnosis of visual impairment in children is given and whether the memory of this event persists over time leading to a flashbulb memory. A longitudinal study was carried out with the participation of 38 mothers. Data were collected on sociodemographics, clinical variables, circumstances surrounding the communication of the diagnosis, and the degree of agreement of the information in the two phases of the research. The diagnosis was, on the whole, given to both parents at the same time, in medical language and with little tact, generally in the office of an ophthalmologist. The mothers would have preferred to have received the news in a different way, and the existence of a flashbulb memory is confirmed, more dependent on the context in which the diagnosis was given and its content than on sociodemographic and clinical factors. The way in which the first news of such a diagnosis is given plays a significant role in how it is remembered. Therefore, an improvement in medical practice regarding the communication of such diagnoses is recommended.